Antibiotics Stewardship in Cesarean Section at a Public Hospital in Surabaya, Indonesia - Herawati, Fauna; Yulia, Rika; Binta, Jihan (Universitas Padjadjaran, 2025)
Cesarean section (CS) is a procedure performed to save the mother and fetus through an incision in the mother’s abdomen and uterus. The high rate of CS in Indonesia correlates with the risk of surgical site infections (SSI), making the use of prophylactic antibiotics important. The use of antibiotics has health impacts on the community, one of which is antibiotic resistance. This study aims to determine antibiotic usage patterns and their compliance with the National Formulary and the Antimicrobial Stewardship Program (PPRA), and the profile of mothers who experience SSI at a public hospital in Surabaya. This retrospective observational quantitative study used medical record data from CS patients from January to June 2024, and the data were analyzed using descriptive statistics and Defined Daily Dose (DDD) methodology to evaluate antibiotic utilization. The results showed cefazolin 2 grams was the most widely used antibiotic (88.64%) with a DDD/100 bed days value of 14.10. Compliance of antibiotic usage patterns with the Antimicrobial Use Guideline (PPAB) reached 88.64%. SSI occurred in 1.31% of patients, especially in pregnancies of more than 2 times. The use of antibiotics at a public hospital in Surabaya is the rational use of antibiotics, the incidence of SSI is smaller than the established standard of 1.5%.